2022
DOI: 10.3847/1538-4357/ac8a47
|View full text |Cite
|
Sign up to set email alerts
|

The 2020 Eclipse of R Aquarii in the Near-infrared: Mid-eclipse Observations of Disk Distress

Abstract: The Mira in the bright, dusty, symbiotic binary R Aquarii undergoes eclipses of multiyear duration every ∼44 yr by a large, opaque accretion disk. The 2020 eclipse was confirmed by I-band photometry. High-resolution M- and K-band spectra were observed near the midpoint of the eclipse, in 2020 August and September. The 4.5–5.5 μm spectrum during eclipse is a complex blend of disk and Mira features. Continuum emission from the disk region contributes to both the 2.3 μm and 4.6 μm region. The lowest energy vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…Recent multiwavelength observations (Bujarrabal et al 2018;Teyssier et al 2019;Willson 2020) strongly suggest that the R Aqr WD companion has been approaching or passing through the periastron since late 2018, several years earlier than predicted by the currently available orbit (Willson et al 1981). The dimming of over 2 mag of the optical light curve (V and B magnitudes, normally dominated by Miraʼs 7 mag amplitude variation) shows the signature of powerful recent mass ejection from Mira, resulting in a significant obscuration of the central region of the system, likely caused by a large dust cloud (Sankrit et al 2022) (see however Hinkle et al 2022, where it is suggested that the periastron passage might occur as late as 2024).…”
Section: Introductionmentioning
confidence: 98%
“…Recent multiwavelength observations (Bujarrabal et al 2018;Teyssier et al 2019;Willson 2020) strongly suggest that the R Aqr WD companion has been approaching or passing through the periastron since late 2018, several years earlier than predicted by the currently available orbit (Willson et al 1981). The dimming of over 2 mag of the optical light curve (V and B magnitudes, normally dominated by Miraʼs 7 mag amplitude variation) shows the signature of powerful recent mass ejection from Mira, resulting in a significant obscuration of the central region of the system, likely caused by a large dust cloud (Sankrit et al 2022) (see however Hinkle et al 2022, where it is suggested that the periastron passage might occur as late as 2024).…”
Section: Introductionmentioning
confidence: 98%